Effect of Local Platelet Rich Fibrin Injection (i-PRF) and Micro Osteo-Perforations (MOPs) on Molar Mesial Movement during Canine Distalization - Wadood; Islam, Ayesha; Hafiz, Maryam; Ahmed, Affaq; Sami, Ramsha; Mukhtar, Mahinoor (Indus Journal of Bioscience Research, 2025)
Background: Adjunctive acceleration techniques such as micro-osteoperforations (MOPs) and injectable platelet-rich fibrin (i-PRF) are increasingly used to enhance orthodontic tooth movement; however, their influence on anchorage loss remains insufficiently defined. Aim: This study evaluated and compared maxillary first molar mesial movement during canine distalization on the MOP and i-PRF sides. Methodology: A single-blinded randomized split-mouth clinical trial was conducted on 32 participants (mean age 22.22 ± 5.15 years). Each participant contributed both intervention sides: MOPs on one side and i-PRF on the contralateral side. Molar mesial movement was measured on dental casts at 1 month (T1), 2 months (T2), and 3 months (T3). Paired t-tests were applied for inter-side comparisons, with stratification by gender and age group. Statistical significance was set at p < 0.05. Results: At T1, molar mesial movement was 0.21 ± 0.04 mm on the MOP side and 0.19 ± 0.02 mm on the i-PRF side (p = 0.120). At T2, mesial movement was significantly higher with MOP (0.40 ± 0.04 mm) than i-PRF (0.38 ± 0.03 mm; p = 0.025). At T3, MOP remained significantly higher (0.70 ± 0.09 mm vs 0.63 ± 0.04 mm; p = 0.002). In males, T3 movement was greater with MOP (0.71 ± 0.08 mm) than i-PRF (0.63 ± 0.04 mm; p < 0.001), while differences in females were non-significant. At T3, significant differences persisted in both age groups: 21–30 years (0.68 ± 0.07 vs 0.63 ± 0.04 mm; p = 0.015) and 13–20 years (0.72 ± 0.11 vs 0.64 ± 0.05 mm; p=0.035). Conclusion: MOPs were associated with slightly greater molar mesial movement than i-PRF during canine distalization, with significant differences emerging over time.